The malaria parasite has an intrinsic clock - Filipa Rijo‐Ferreira; Victoria A. Acosta-Rodríguez; John H. Abel; Izabela Kornblum; Inês Bento; Gokhul Kilaru; Elizabeth B. Klerman; Maria M. Mota; Joseph S. Takahashi (2020)
Malarial rhythmic fevers are the consequence of the synchronous bursting of red blood cells (RBCs) on completion of the malaria parasite asexual cell cycle. Here, we hypothesized that an intrinsic clock in the parasite